Enhanced Recovery Stem-Cell Transplantation: Multidisciplinary Efforts to Improve Outcomes in Older Adults Undergoing Hematopoietic Stem-Cell Transplant. Issue 3 (10th March 2023) - Ngo-Huang, An; Ombres, Rachel; Saliba, Rima M.; Szewczyk, Nicholas; Adekoya, LaToya; Soones, Tacara N.; Ferguson, Jill; Fontillas, Rhodora C.; Gulbis, Alison M.; Hosing, Chitra; Kebriaei, Partow; Lindsay, Richard; et al.
Abstract : PURPOSE: Older adults have unique risk factors for poor outcomes after hematopoietic stem-cell transplant (HSCT). We sought to determine the impact of our multidisciplinary supportive care program, Enhanced Recovery after stem-cell transplant (ER-SCT), on survival outcomes in patients age 65 years and older who underwent HSCT. PATIENTS AND METHODS: In this retrospective study, clinicodemographic data, nonrelapse mortality (NRM), overall survival (OS), and relapse were compared between 64 patients age 65 years and older who underwent allogeneic stem-cell transplant during ER-SCT program's first year, October 2017 through September 2018, and 140 historical controls age 65 years and older who underwent allogeneic HSCT, January 2015 through September 2017. RESULTS: In the ER-SCT cohort, 41% (26 of 64) of patients were women, and the median (range) age was 68 (65-74) years; in the control cohort, 38% (53 of 140) of patients were women, and the median (range) age was 67 (65-79) years. Hematopoietic cell transplant comorbidity index and donor type/cell source were similar between cohorts. The ER-SCT cohort had a lower 1-year NRM rate (13% v 26%, P = .03) and higher 1-year OS rate (74% v 53%, P = .007). Relapse rate did not differ significantly between cohorts. In multivariate analyses, ER-SCT was associated with improved 1-year NRM (hazard ratio, 0.4; 95% CI, 0.2 to 0.9; P = .02) and improved 1-year OS (hazard ratio, 0.5; 95% CI, 0.3 to 0.9; P = .03). CONCLUSION: A multidisciplinary supportive care program may improve NRM and OS in older patients undergoing allogeneic HSCT. Randomized studies are warranted to confirm this benefit and explore which program components most contribute to the improved outcomes.